2013
DOI: 10.1007/s10103-013-1417-z
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG laser in occlusal caries prevention of primary teeth: A randomized clinical trial

Abstract: Dental caries is still the most prevalent chronic disease affecting human populations. Among the preventive treatments performed, it has been reported that laser irradiation combined with topical fluoride can induce an even greater increase in enamel caries resistance. The aim of this study was to evaluate the Nd:YAG laser, with or without fluoride, in occlusal caries prevention of the primary dentition. A double-blind split-mouth study design was used. Fifty-two children with high caries risk (7.6 ± 1.4 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
2
23
0
8
Order By: Relevance
“…To corroborate to this fact, the profilometric analysis performed after treatments showed that there were no surface loss after laser irradiation. Nonetheless, Nd:YAG laser irradiation alone, with Many studies have shown beneficial effects of the Nd:YAG laser irradiation against enamel demineralization [29][30][31], but these findings are mostly related to dental caries. Considering the more aggressive nature of the acid challenges associated to the erosion process, we may suppose that the laser-modified surface, created by the Nd:YAG laser on the parameters used in this study, may have been rapidly removed, offering no long-term protection.…”
Section: Discussionmentioning
confidence: 96%
“…To corroborate to this fact, the profilometric analysis performed after treatments showed that there were no surface loss after laser irradiation. Nonetheless, Nd:YAG laser irradiation alone, with Many studies have shown beneficial effects of the Nd:YAG laser irradiation against enamel demineralization [29][30][31], but these findings are mostly related to dental caries. Considering the more aggressive nature of the acid challenges associated to the erosion process, we may suppose that the laser-modified surface, created by the Nd:YAG laser on the parameters used in this study, may have been rapidly removed, offering no long-term protection.…”
Section: Discussionmentioning
confidence: 96%
“…The use of lasers in preventive dentistry seems to be effective in children caries prevention. Raucci‐Neto et al () reported a lower incidence of caries in children with high caries‐risk over a period of 1 year when the laser treatment was applied on occlusal surfaces. Furthermore, Er:YAG laser treatment has a caries‐preventive effect on primary teeth through reduction of carbonate and modification of organic matter (Liu & Hsu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Laser re-crystalizes and fuses the enamel prisms and by changing the organic structure of enamel, decreases its acid solubility and confers caries resistance to tooth structure. [27][28][29] However, since the application of laser requires costly equipment, 7 the possibility of laser enhancing the preventive effect of fluoride must be carefully investigated considering the above-mentioned limitations of laser. The current in vitro, experimental study compared the reduction in surface area of 60 WSLs on the crowns of 20 extracted primary teeth in 3 groups of control, 1.23% APF gel and Er,Cr,YSGG laser in combination with 1.23% APF gel.…”
Section: Discussionmentioning
confidence: 99%